2003
DOI: 10.1023/a:1025405216339
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Conners' Continuous Performance Test (CPT) is a neuropsychological task that has repeatedly been shown to differentiate ADHD from normal groups. Several variables may be derived from the Conners' CPT including errors of omission and commission, mean hit reaction time(RT), mean hit RT standard error, d', and beta. What each CPT parameter actually assesses has largely been based upon clinical assumptions and the face validity of each measure (e.g., omission errors measure inattention, commission errors measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
125
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(141 citation statements)
references
References 22 publications
16
125
0
Order By: Relevance
“…Commission errors refer to discrete instances in which children respond incorrectly to non-target stimuli, and demonstrate moderate convergent validity with diverse indices of impulsivity (r00.20 to 0.45). These indices include parent ratings (Avila et al 2004;Barkley 1991;Nigg et al 1996;Olson et al 1999), teacher ratings (Barkley 1991;Brewis 2002;Halperin et al 1991;Halperin et al 1988; Klee and Garfinkel 1983), clinical diagnostic interviews (Epstein et al 2003), direct observations of impulsive behavior while completing academic assignments (Barkley 1991), and composite indices of direct observations, parent/ teacher reports, and self-report (Moffitt et al 2011).…”
mentioning
confidence: 67%
“…Commission errors refer to discrete instances in which children respond incorrectly to non-target stimuli, and demonstrate moderate convergent validity with diverse indices of impulsivity (r00.20 to 0.45). These indices include parent ratings (Avila et al 2004;Barkley 1991;Nigg et al 1996;Olson et al 1999), teacher ratings (Barkley 1991;Brewis 2002;Halperin et al 1991;Halperin et al 1988; Klee and Garfinkel 1983), clinical diagnostic interviews (Epstein et al 2003), direct observations of impulsive behavior while completing academic assignments (Barkley 1991), and composite indices of direct observations, parent/ teacher reports, and self-report (Moffitt et al 2011).…”
mentioning
confidence: 67%
“…In dimensional analyses, Epstein et al (2003) found that RT variability was related to both symptoms of hyperactivity/impulsivity and symptoms of inattention, but this study failed to control for the overlap between symptom domains. Clarke et al (2007) did conduct such a control in analyses investigating independent as well as interaction effects in the two symptom domains.…”
Section: Adhd and State Regulationmentioning
confidence: 99%
“…During tasks requiring vigilance, these resources declined, which caused a decrease in performance efficiency (Warm, Parasuraman, & Matthews, 2008). Sustained attention has been found to be the major factor in explaining the difficulties of attention-deficit hyperactivity disorder (ADHD) (to name only a few studies: Epstein et al, 2003;Johnson et al, 2007;Tsal et al, 2005). Investigation into sustained attention increased significantly with the introduction of computerized testing (computerized testing is a part of a testing procedure named: continuous performance tests (CPTs)).…”
mentioning
confidence: 99%